Distúrbios de sono e o risco de disfunções temporomandibulares : revisão sistemática de literatura e metanálise - Roithmann, Camila Caspary (2020)
Introduction: According to the American Academy of Orofacial Pain, temporomandibular disorders (TMD) are defined as a "group of disorders involving the masticatory muscles, the temporomandibular joint (TMJ) and associated structures". Efforts have been made in order to identify related disorders concerning TMD's multifactorial etiology, with the purpose of providing the best healthcare for the patients in need. Among those conditions, sleep disorders stand out. Objectives: This study aims to evaluate the relation between sleep disorders and TMD based on the available literature, as well as to verify the distribution of sleep disorders in the different diagnostic groups presented by the DC/TMD questionnaire. Methods: A systematic review was performed in the PubMed, Embase, Lilacs, Web of Science, Scielo, Cinahl and Cochrane Central databases. Manual search and gray literature search were also performed. Only observational studies that were published since 1992 were included. Two reviewers participated independently. Quality analysis on the included papers was conducted according to the Ottawa-Newcastle Scale. The extracted data were submitted to heterogeneity calculation, publication bias analysis and meta-analysis. Results: 1071 articles were found after the online search. 3 papers were added manually. Duplicate exclusion was carried out. According to the eligibility criteria, 131 articles were selected for full-text reading. 29 were included in the final work and 20 in the meta-analysis. The forest plots indicate a positive relationship between sleep disorders and TMD in all DC/TMD diagnostic groups, except for axis 1 group II (disc displacements). Limitations: Publication bias, absence of data for control groups in 9 articles, exclusion of articles that used polysomnography as a diagnostic tool for sleep disorders. Conclusions: Based on the obtained results, there is a positive relationship between sleep disorders and TMD (except for the diagnosis of disc displacements). There is a 3.48 times increased risk of TMD (Odds Ratio) for individuals who suffer from sleep disorders compared to those without this diagnosis.